В поисках современной управленческой парадигмы - Нагорный, Б. (Социология: теория, методы, маркетинг, 2000)
Management system of transitional society needs to be analysed by specialists in order to define the character of relations between subjects and objects of management. The author is trying to clarify the main criteria for assessment of different managerial groups activity and to find safe the ground for working out new management paradigm and effective social technologies.